BS EN IEC 62841-3-8 AMD1. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-8. Particular requirements for transportable single spindle vertical moulders (17th February 2022) - British Standards Institution,
No abstract available